The anthropology of peace and reconciliation - Eltringham, Nigel, author.
1 online resource
Keywords: This book offers a uniquely comparative, case-study perspective on the anthropology of peace and reconciliation. In the contemporary world, the end of violent conflict often gives way to one, or a combination, of five interventions designed to strengthen peace and facilitate reconciliation. These interventions are: the reinvigoration of traditional conflict management mechanisms; the collection and preservation of testimony; truth commissions; international criminal trials; and memorialisation. Social anthropologists have challenged the received wisdom on which these interventions are based, arguing that they fail to adequately take into account and sensitively manage the needs and expectations of those who have lived through conflict. Exploring the five interventions through detailed ethnographic accounts from around the world, this book demonstrates that although social anthropologists adopt a critical stance, they do not dismiss received wisdom out of hand; rather, theyadvocate that interventions should be subject to continuous evaluation according to the evolving, often contradictory, needs and wishes of those who strive to survive among the ruins of their former lives. This is essential reading for scholars of peace studies, conflict resolution studies and those taking an anthropological approach to conflict, violence, human rights and law.